Correction to: Mercury Exposure: Protein Biomarkers of Mercury Exposure in Jaraqui Fish from the Amazon Region (Biological Trace Element Research, (2018), 183, 1, (164-171), 10.1007/s12011-017-1129-5) - Vieira, José Cavalcante Souza [UNESP]; Braga, Camila Pereira [UNESP]; de Oliveira, Grasieli [UNESP]; do Carmo Federici Padilha, Cilene [UNESP]; de Moraes, Paula Martin [UNESP]; Zara, Luiz Fabricio; de Lima Leite, Aline; Buzalaf, Marília Afonso Rabelo; de Magalhães Padilha, Pedro [UNESP] (Springer Nature, 2018)
In the affiliation section, Luiz Fabricio Zara's affiliation “Pontifical Catholic University of Goiás (PUC), Goiânia, GO, Brazil” was incorrect. The correct affiliation is College of Planaltina, UnB - University of Brasília, Distrito Federal, Brazil.